Analysis of Relationship Pattern Between Strategic Orientation of Enterprise Business and Strategic Orientation of Information System - Edy Prayitno; Heru Agus Triyanto; Budhi Dharmawan (AIBPM Publisher, 2019)
This study aims to determine the alignment of the relationship between business strategies and information systems strategies in a company. This study uses a questionnaire that asks respondents to answer questions about aligning the relationship between the observed variables, namely business strategy and information system strategy. The results of respondents' answers were tested for data quality with validity and reliability. By using valid and reliable data, the correlation test is performed using the Kendall correlation coefficient. The results showed the relationship between the company's business strategy with the existing information system strategy.